Infrastruktur, Aksi Kolektif, dan Nilai-Nilai Islam: Telaah Manajemen Operasional Program TMMD di Desa Selat Beting - Henni Setiani; Aqwa Nasser Daulay; Muhammad Yafiz (Jurnal Ilmiah Mahasiswa Raushan Fikr, 2025)
This study analyzes the operational management of the TMMD program in enhancing the efficiency and effectiveness of infrastructure development in Selat Beting Village, Labuhanbatu Regency. A qualitative descriptive method was employed, utilizing William N. Dunn’s policy evaluation framework. Data were collected through observation, interviews, and documentation to assess the management performance of this government program. The findings demonstrate that the TMMD program has been implemented effectively with an achievement rate of 103 percent and efficiently with a ratio of 4.38 kilometers per rupiah through proper planning, execution, and supervision. Efficiency was achieved by optimizing resources and fostering cross-sector collaboration, while effectiveness was reflected in improved access, infrastructure quality, and community participation. From an Islamic economics perspective, the program embodies the principles of justice, trustworthiness (amanah), prohibition of wastefulness (israf), collective cooperation (taawun), and the pursuit of public welfare (maslahah).